The Textual Criticism and Structural Analysis of Noorbakhshi’s Adab-e- Insha in the Rhetoric of Prose and the Epistolary of the Safavid Era - amir jahadi (مطالعات زبانی و بلاغی)
The issue of the present paper is, to investigate the Adab e Inshae written by Norbakhshi. This work is also recorded as the Inshay e alam Ara. Adab e Inshae deals with the theoretical approach to the issue of Epistolary in the Safavid era.  The present work is classified into a coherent structure; the first Section of this book is introduction as a Fatiha.  It consists of three chapters as a Lamae and the final section as Khatimah. The author's perspective on this text is a rhetorical review of Epistolary Persian prose. There are six manuscripts from this work. This text is only a part of the introduction and the beginning of the first chapter. The author's particular method in the present work is unique among the works of the others, because he considered Persian prose with an exclusive approach to Persian prose Epistolary. In addition, the literary techniques which required by the secretaries are described in an example. In the Safavid era, technical prose is highly regarded by writers. The examples cited are often prose and sometimes poetry. Norbakhshi is the poet of the Safavid era and his pseudonym has been Sayyed. At the beginning of the text, the characteristics of the secretaries of the court are enumerated. The author of this article has tried to study textual aspects at first instance, and then examines the structure and content of the effect. The article will also describe the author's description of the book. The final part of the article is devoted to the study of the style of the work.